Lack of early etiologic investigations in young sudden cardiac death. (October 2022) - Sharifzadehgan, Ardalan; Gaye, Bamba; Bougouin, Wulfran; Narayanan, Kumar; Dumas, Florence; Karam, Nicole; Rischard, Julien; Plu, Isabelle; Waldmann, Victor; Algalarrondo, Vincent; Gandjbakhch, Estelle; Bruneval, Patrick; et al.
Abstract: Background: Since majority of sudden cardiac arrest (SCA) victims die in the intensive care unit (ICU), early etiologic investigations may improve understanding of SCA and targeted prevention. Methods: In this prospective, population-based registry all SCA admitted alive across the 48 hospitals of the Paris area were enrolled. We investigated the extent of early etiologic work-up among young SCD cases (<45 years) eventually dying within the ICU. Results: From May 2011 to May 2018, 4, 314 SCA patients were admitted alive. Among them, 3, 044 died in ICU, including 484 (15.9%) young patients. SCA etiology was established in 233 (48.1%) and remained unexplained in 251 (51.9%). Among unexplained (compared to explained) cases, coronary angiography (17.9 vs. 49.4%, P < 0.001), computed tomography scan (24.7 vs. 46.8%, P < 0.001) and trans-thoracic echocardiography (31.1 vs. 56.7%, P < 0.001) were less frequently performed. Only 22 (8.8%) patients with unexplained SCD underwent all three investigations. SCDs with unexplained status decreased significantly over the 7 years of the study period (from 62.9 to 35.2%, P = 0.005). While specialized TTE and CT scan performances have increased significantly, performance of early coronary angiography did not change. Autopsy, genetic analysis and family screening were performed in only 48 (9.9%), 5 (1.0%) and 14 cases (2.9%) respectively. Conclusions: More than half of young SCD dying in ICU remained etiologically unexplained; this was associated with a lack of early investigations. Improving early diagnosis may enhance both SCA understanding and prevention, including for relatives. Failure to identify familial conditions may result in other preventable deaths within these families.